2017
DOI: 10.3390/nu9060581
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Integrated Infant and Young Child Feeding and Micronutrient Powder Intervention on Feeding Practices and Anemia in Children Aged 6–23 Months in Madagascar

Abstract: This study assesses the impact of an integrated infant and young child feeding (IYCF) and micronutrient powder (MNP) intervention on children’s risk of anemia and IYCF practices in Madagascar. Quantitative baseline and endline surveys were conducted in representative households with children 6–23 months from two districts, where an 18-month IYCF-MNP intervention was implemented. Relative risks comparing children’s risk of anemia and maternal IYCF knowledge and practices at baseline versus endline, and also at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 28 publications
3
43
1
Order By: Relevance
“…Differences in coverage by age in our analyses might be explained by caregiver perception of reduced risk of micronutrient malnutrition among older children and/or need for micronutrient supplementation in the Ugandan context. Our findings are contrary to studies where children 12–17 and 18–23 months had higher MNP consumption (Madagascar) and greater odds of obtaining MNP (Nepal) relative to children 6–11 months (Jefferds et al, ; Locks et al, ). However, our analyses did not include children 6–11 months, thus may not be comparable.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Differences in coverage by age in our analyses might be explained by caregiver perception of reduced risk of micronutrient malnutrition among older children and/or need for micronutrient supplementation in the Ugandan context. Our findings are contrary to studies where children 12–17 and 18–23 months had higher MNP consumption (Madagascar) and greater odds of obtaining MNP (Nepal) relative to children 6–11 months (Jefferds et al, ; Locks et al, ). However, our analyses did not include children 6–11 months, thus may not be comparable.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to findings from MNP studies in Nepal and Madagascar (Mirkovic et al, ; Locks et al, ), children's perceptions of foods mixed with MNP were associated with coverage and recent intake. Children whose caregivers reported the child liked or was neutral about consuming foods mixed with MNP had nearly two‐times higher odds of recent intake relative to children whose caregivers reported the child disliked foods mixed with MNP.…”
Section: Discussionsupporting
confidence: 73%
“…This allows for both growing familiarity with the intervention and continued improvements in nutritional status, building on the previous years' gains, to be assessed. Although disruption to MNP distribution in 2015 likely hindered this process, this is a problem commonly encountered by others too (Christofides, Schauer, Sharieff, & Zlotkin, ; Locks, Reerink, & Tucker Brown, ; Mirkovic et al, ). The primary limitation of our study is that although our results were consistent across the surveys and methods used, the data are largely based on parent reports of adherence and acceptability and could be subject to social desirability bias.…”
Section: Discussionmentioning
confidence: 96%
“…FCHVs often interact with mothers more frequently and for longer durations than facility‐based health workers and are thus better positioned to deliver consistent IYCF‐MNP counselling and to help mothers troubleshoot as challenges arise. Other studies have also shown that community health workers are a viable and reliable channel for the delivery of MNP and IYCF‐MNP counselling (Locks et al, ; Olney et al, ). The reiteration of key messages through facility‐based health workers can complement community‐based counselling; however, our findings highlight that community health worker counselling may be especially important for supporting a deep understanding of how to use MNP and for supporting sustained use.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of maternal report of organoleptic changes may be a sign of inappropriate preparation of foods with MNP by mothers (such as adding MNP to hot foods, soups or other liquids, and/or very small portions of food; Tumilowicz et al, ); however, we did not find in this analysis that knowledge of appropriate use was associated with maternal report of organoleptic changes. Other MNP interventions have encountered product quality issues that resulted in organoleptic changes to food (Locks et al, ; Schauer et al, ). Taken together, these findings highlight the importance of not only ensuring a high quality MNP product (Schauer et al, ) but also incorporating behaviour change strategies that support mothers as they try different strategies to encourage the child to eat foods with MNP, such as mixing with highly flavourful foods such as bananas or curry, making sure the amount of food served to the child is sufficient to thoroughly mix in the MNP, or adding MNP to the child's food without their knowledge (Jefferds et al, ).…”
Section: Discussionmentioning
confidence: 99%